Genetic correlation between circulating metabolites and chalazion: a two-sample Mendelian randomization study - Zhang, Xin; Cai, Yuying; Jiang, Yaping; Du, Wei; An, Weishu; Fu, Qiangqiang; Chen, Yihui (Frontiers in Molecular Biosciences, 2024)
Background: Lipid metabolism disorders were observationally associated with chalazion, but the causality of the related circulating metabolites on chalazion remained unknown. Here, we investigated the potential causal relationship between circulating metabolites and chalazion using two-sample Mendelian randomization (MR) analysis. Methods: For the primary analysis, 249 metabolic biomarkers were obtained from the UK Biobank, and 123 circulating metabolites were obtained from the publication by Kuttunen et al. for the secondary analysis. Chalazion summary data were obtained from the FinnGen database. Inverse variance weighted (IVW) is the main MR analysis method, and the MR assumptions were evaluated in sensitivity and colocalization analyses. Results: Two MR analyses results showed that the common metabolite, alanine, exhibited a genetic protective effect against chalazion (primary analysis: odds ratio [OR] = 0.680; 95% confidence interval [CI], 0.507–0.912; P = 0.010; secondary analysis: OR = 0.578; 95% CI, 0.439–0.759; P = 0.00008). The robustness of the findings was supported by heterogeneity and horizontal pleiotropy analysis. Two colocalization analyses showed that alanine did not share a region of genetic variation with chalazion (primary analysis: PPH4 = 1.95%; secondary analysis: PPH4 = 25.3%). Moreover, previous studies have suggested that an increase in the degree of unsaturation is associated with an elevated risk of chalazion (OR = 1.216; 95% CI, 1.055–1.401; P = 0.007), with omega-3 fatty acids (OR = 1.204; 95% CI, 1.054–1.377; P = 0.006) appearing to be the major contributing factor, as opposed to omega-6 fatty acids (OR = 0.850; 95% CI, 0.735–0.982; P = 0.027). Conclusion: This study suggests that alanine and several unsaturated fatty acids are candidate molecules for mechanistic exploration and drug target selection in chalazion.